Influence of Hybrid Reactive Power Compensation on the Secondary Arc of Ultra-High-Voltage Transmission Lines (May 2018) - Hongshun Liu; Jingjing Yang; Liang Ji; Zhen Wang; Zhenning Huang; Xiaoshuai Yang; Jiangtao Wang (IEEE Access, 2018)
Hybrid reactive power compensation (HRPC) which consists of series compensation and a stepped-controlled shunt reactor will see use in China's future ultra-high-voltage (UHV) transmission system. As a result, some new characteristics of the secondary arc during a single-phase-to-ground fault on UHV transmission lines with HRPC may be raised. In this paper, the secondary arc characteristics during the single-phase auto-reclosure (SPAR) operation have been simulated with regard to the UHV AC system installed with HRPC. Based on the UHV system model with HRPC and its secondary arc model, the influence mechanism of HRPC on secondary arc current is theoretically derived with the simulated waveforms and the Fourier analysis. Besides, the relationship among the secondary arc current, the arcing time with different HRPC compensation degrees, neutral reactance, as well as the grounding fault locations have been investigated in detail. Finally, an improved time sequential control strategy of bypass breaker and SPAR has been put forward. The research presented in this paper will provide necessary theoretical basis and technical support for the future application of HRPC in UHV transmission lines.